Analisis Peran Pembiayaan Lembaga Keuangan Syariah pada Sektor Pertanian di Kabupaten Brebes - Nurlaeli, Fenti; Mubtadi, Novendi Arkham; Abdilah, Alya Isni (Velocity: Journal of Sharia Finance and Banking, 2021)
Islamic financial institution have a princip of balanced (tawazun) with do business and social activity. This research aims to analyze the role of Islamic financial Institution on financing for the agricultural sector in Brebes Central Java Province, to analyze the obstacle and the potential product which is financially granted by Islamic financial Institution for the agricultural sector. This research took explorative-qualitative approach to find more and depth on another possibility of the problem of object research. The informants was taken from three Islamic financial Institutions in Brebes regency. The result shows the role of Islamic financial institution is not maximal. This is because (1) agricultural sector depends on the nature (2) Islamic financial Institution as a trustee. The potential of Islamic financial institution is on the availability of financial contract such as murobahah, musawamah, salam, muzara’ah and tawaruq.